Chronic exercise training effects on immune function - MacKinnon, L. T. (Medicine & Science in Sports & Exercise, 2000)
Purpose: This paper reviews the recent literature on the chronic effects of exercise training on immune function in humans. There is a general perception by athletes and other physically active individuals that regular moderate activity enhances, whereas intense exercise suppresses, resistance to minor illnesses such as upper respiratory tract infection (URTI). This perception is supported by epidemiological data in endurance athletes and limited data from intervention studies using moderate exercise in previously untrained individuals. The apparently high incidence of URTI among endurance athletes has prompted interest the relationship between chronic exercise training and immune function. Whereas immune cell number is generally normal during intense exercise training, recent evidence suggests that prolonged periods of intense training may lead to slight impairment in immune parameters such as neutrophil function, serum and mucosal immunoglobulin levels, plasma glutamine concentration, and possibly natural killer cell cytotoxic activity. In contrast, moderate exercise training has either no effect on, or may stimulate, these immune parameters. Conclusion: Whereas athletes are not clinically immune deficient, it is possible that the combined effects of small changes in several immune parameters may compromise resistance to minor illnesses such as URTI. Strategies to prevent URTI in athletes include avoiding overtraining, providing adequate rest and recovery during the training cycle and after competition, limiting exposure to sources of infection, ensuring adequate nutrition, and possibly vitamin C supplementation. It is uncertain at present whether moderate exercise training is helpful in preventing infectious illness among the wider population.